AIHce 2003 2003
DOI: 10.3320/1.2757901
|View full text |Cite
|
Sign up to set email alerts
|

223. Development of an Abbreviated Qualitative Fit Test Using Bitter Aerosol

Abstract: Occupational Safety and Health Administration (OSHA) regulation 29 CFR 1910.134 respiratory protection, requires qualitative fit tests (QLFT) to consist of seven, one minute exercises. This procedure is time consuming, and the benefit of the exercise duration is unknown. This study evaluated a bitter (Bitrex™) aerosol fit test with 15 second exercises. The shortened test was compared to a generated aerosol quantitative fit test (QNFT) using one minute exercise times. Results show that the shortened test has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In contrast, the study by Hardis et al and Nelson et al 26 , 32 ) , showed that most of the American subjects passed the IAA fit tests. Meanwhile, Skretvedt et al stated that 98% of the clean-shaven subjects passed the IAA fit tests; however, the bearded subjects were considerably more at risk than the clean-shaven ones 33 ) .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, the study by Hardis et al and Nelson et al 26 , 32 ) , showed that most of the American subjects passed the IAA fit tests. Meanwhile, Skretvedt et al stated that 98% of the clean-shaven subjects passed the IAA fit tests; however, the bearded subjects were considerably more at risk than the clean-shaven ones 33 ) .…”
Section: Discussionmentioning
confidence: 85%
“…It draws the conclusion that the IAA fit test could be considered as an acceptable procedure for assessing the leakage into the respirators. According to the previous study, the IAA fit testing protocol was considered as a safe and valid procedure for qualitative assessment of the leakage into the respirator 25 , 26 ) . Han et al evaluated the IAA fit test compared to the condensation nuclei counter (CNC) QNFT procedure and showed that the IAA fit test passing rate was 72.70%.…”
Section: Discussionmentioning
confidence: 99%
“…Respirator fit testing was performed using the 3M Fit Test Kit FT-31 (3M Canada Company, Ontario, Canada) (denatonium benzoate solution). [4] In the procedure for the respirator fit testing program, [5] the 1st part of the test is to screen the ability of the examinee to detect (taste) aerosolized droplets of a dilute solution of denatonium benzoate; then the examinee wears the respirator for the 2nd part of the test, and a more concentrated solution of the denatonium benzoate is sprayed into the hood while the individual performs a set of actions. The test criterion of the respirator fit test is the failure to taste the denatonium benzoate by the examinee.…”
Section: Case Reportmentioning
confidence: 99%
“…(2) The generated aerosol QNFT has been used as the reference method for validation of the other common fit-tests, including the ambient particle and controlled negative pressure QNFT and the Bitrex QLFT. (3)(4)(5)(6)(7)(8)(9) However, these common fit-tests have not been extensively compared with one another. In addition, the generally accepted ''passing'' quantitative fit factors for half-and full-facepiece respirators are based on multiplying the APF for negative pressure configurations of those respirators by an arbitrary safety factor of 10.…”
mentioning
confidence: 99%